Gender Nonconformity, Sexual Orientation, and Dutch Adolescents’ Relationship with Peers - Bos, Henny (Arch Sex Behav, 2014)
Same-sex attraction and gender nonconformity have both been shown to negatively affect the relationships of adolescents with their peers. It is not clear, though, whether same-sex attracted adolescents are more likely to have negative peer relationships because they are same-sex attracted or because they are more likely to be gender nonconforming. It is also possible that both stressors affect peer relationships independently or amplify each other in their impact. We explored these questions in a sample of 486 Dutch adolescents (M age = 14.02 years). We found that same-sex attraction and gender nonconformity both had an independent effect and that gender nonconformity moderated, but not mediated, the associations between same-sex attraction and peer relationships at school. Same-sex attraction was more strongly associated with poorer relationships with peers in adolescents who were more gender nonconforming. These findings indicate the importance of including gender nonconformity in the understanding of same-sex attracted adolescents’ relationships and suggest that in order to improve same-sex attracted adolescents’ social position at school, acceptance of gender diversity should be promoted as well.